1991
DOI: 10.3109/01485019108987623
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interactions of Eutherian Ova/Spermatozoa: Significance for Orientation/Binding of Gametes

Abstract: Ova are observed in vitro to rotate counterclockwise immediately following sperm attachment. This phenomenon was examined in both human-hamster and hamster-hamster systems. The counterclockwise rotation has been found to be directly proportional to the efficiency of in vitro penetration or fertilization. These observations indicate that the eutherian ova possess a definite polarity and that the sperm attachment follow a given geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Thus, using these estimates in eqn (37), we obtain +50/N. It is clear that a minimal amount of spermatozoa attempting penetration, that is naturally 178 A. NIR accumulated at a very early stage after insemination, will render the value of (1 and that a rotation of the cluster can be expected soon after the encounter began, in agreement with the reported observations (Nilsson et al, 1986;Kamiguchi and Mikamo, 1986;Rosenbush et al, 1989;Chaudhuri et al, 1991). Furthermore, since the model predicts that the intensity of rotation is proportional to (1!…”
supporting
confidence: 80%
See 4 more Smart Citations
“…Thus, using these estimates in eqn (37), we obtain +50/N. It is clear that a minimal amount of spermatozoa attempting penetration, that is naturally 178 A. NIR accumulated at a very early stage after insemination, will render the value of (1 and that a rotation of the cluster can be expected soon after the encounter began, in agreement with the reported observations (Nilsson et al, 1986;Kamiguchi and Mikamo, 1986;Rosenbush et al, 1989;Chaudhuri et al, 1991). Furthermore, since the model predicts that the intensity of rotation is proportional to (1!…”
supporting
confidence: 80%
“…Rather, we are concerned here with the slow rotation of the entire cluster of ovum and the spermatozoa that adhere to its external periphery just before penetration. This rotation was observed and documented in vivo (Nilsson et al, 1986) and was reported in various in vitro experiments (Kamiguchi & Mikamo, 1986;Rosenbush et al, 1989;Chaudhuri et al, 1991). The various studies report that the rotation phenomenon exists for eggs with intact cumulus or eggs with exposed zona pellucida as well as for zona free ova.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations